Beyond bus fare: deconstructing prenatal care travel among low-income urban mothers through a mix methods GIS study. Issue 3 (4th May 2018) - Bloch, Joan Rosen; Cordivano, Sarah; Gardner, Marcia; Barkin, Jennifer
Abstract : Objective: Guided by critical theory, this study illustrates the value of interpretative mapping to deconstruct bus travel to publicly funded prenatal care in a city marked by health and social inequities. Methods: This mixed methods study used GIS maps based on 61, 305 births to study the known barrier of transportation to prenatal care among urban mothers most at risk for preterm birth. Results: Among 350 census tracts, 36 census tracts had preterm rates between 25 –36.9%. Modeling travel time for the case vignette for routine prenatal care took 21 visits to different geographically located facilities. This burden increased to 32 visits if the case vignette was high-risk. Conclusions: Interpretative GIS mapping is an important tool to ground truth spatially linked data into real world meanings. Promoting optimal health requires innovative and feasible approaches that take into consideration daily maternal functioning as pregnant mothers care for their children and themselves.